Implementasi Pendekatan Matematika Realistik (PMR) untuk Meningkatkan Kemampuan Pemahaman Konsep Matematis di Kelas VII SMP - Panjaitan, Simon Maruli; Simbolon, Lolyta Damora; Tarigan, Natalia Perbina Br (Lembaga Sosial Rumah Indonesia, 2024)
Purpose – This research aims to determine whether there is an increase in students' ability to understand mathematical concepts through the application of the Realistic Mathematics Learning (PMR) approach to congruence material at SMP N 1 Sei Bingai. This research is Classroom Action Research (PTK) using the Kemmis & Mc Taggart model, which was carried out in 2 cycles, each cycle consisting of several stages, namely: planning, implementation, observation, and reflection. The subjects of this research were 32 students in class VII-4 of SMP N 1 Sei Bingai.Method – The research method used in this research uses a quantitative experimental method to look for the effects found from the realistic mathematical approach treatment of two variables, namely the independent variable and the dependent variable, where the research data is in the form of numbers and the analysis uses statistical calculations.Findings – The findings of this research indicate that applying the Realistic Mathematics Learning (PMR) approach to alignment material can improve students' ability to understand mathematical concepts. In realistic mathematics learning (PMR), the teacher acts as a facilitator so that he can involve and guide students in seeking knowledge in various contextual problem situations. that the application of a realistic mathematics learning approach (PMR) to congruence material can improve students' ability to understand mathematical concepts. The student's classical learning completeness gain at the end of cycle I reached a percentage of 15.625% then increased at the end of cycle II to 71.875% in the medium group with an average N-Gain of 0.407. Research Implications – This research implies that teachers need to further improve and apply teaching methods and use approaches that can increase student understanding.